Mitigated Pilot Contamination to Achieve Higher Downlink Data Rate in 5G Massive MIMO Systems - Salh, Adeeb; Audah, Lukman; Mohd Shah, Nor Shahida; Hamzah, Shipun Anuar (International Journal of Integrated Engineering, 2020)
Massive multiple-input, multiple-output (M-MIMO) is an important knowledge for fifth-generation (5G) wireless cellular networks. The pilot contamination (PC) is an issue in massive MIMO due to interference between adjacent cells. We proposed that the number of pilot sequence inside a cell could become smaller than or equal to the number of users (UEs), taking into account the different number of UEs that transmitted the same pilot sequence in the same cell. In addition, the pilot sequence became mutually orthogonal for different cells to prevent PC among cells. In this paper, we analyzed a channel estimation for time division duplex (TDD) and improved the achievable data rate by reducing the PC for limiting user capacity and using channel orthogonality for minimum mean square error (MMSE) precoding. From the simulation results, the proposed scheme provided a data rate for two several situations, with and without interference PC for an increased number of antennas. Consequently, increasing the number of coherence intervals made the channel estimation critical and provided a small data rate due to increased noise and interference at increased transmit pilot sequence.